Agribusiness Involvement in Local Agriculture as a ‘White Knight’? : A Case Study of Dole Japan’s Fresh Vegetable Business - Sekine, Kae; Hisano, Shuji (The International Journal of Sociology of Agriculture and Food, 2009)
In the past two decades, Japanese agriculture has been shrinking under policies of deregulation, with domestic production being replaced rapidly by imports, in which multinational agribusinesses are key players. Today there is an increasing presence of multinational corporations in Japanese rural sites. Dole Japan, a subsidiary of Dole Food Company, launched a domestic vegetable business in 2000 by organising their own franchise farms and distributing their products with the ‘I Love’ brand through their own supply chain. Although Dole Japan was expected to play the role of a ‘white knight’ in salvaging crumbling local agriculture, it has closed down some farm corporations in regions where it was not successful. Our focus in this article is on the interaction of (1) power, in which Dole Japan plays a dominant role in several rural sites, (2) market response (increasing demand for quality control and traceability), (3) political changes (deregulation), and (4) expectations from rural communities. We will also explore the limitations of the concepts of ‘domestic’ and ‘safety’ in sustaining agriculture and rural economies and will offer the concept of ‘locality’ as an alternative space of food politics.